(untitled) (Applied Biological Research, 2023)
In present study, the industrial applications of red pigment prodigiosin, extracted from Serratia marcescens, were explored. Twelve textile fabric samples (santoon, georgette, bubble, cotton 20/20, cotton polyester, lycra, butter crape, hosiery, satin, linen, cotton and polyester) were used to check the fabrics staining potential of prodigiosin under acidic, basic and neutral conditions. Out of the selected fabrics, the pigment gave attractive red shade to bubble, hosiery, cotton 20-20 and lycra in all the sets. Colour intensity decreased in santoon, cotton polyester, cotton and polyester. Very faint colouration was noticed in satin, linen, butter crape and georgette. Application of prodigiosin as food colorant in bakery products revealed successful use of pigment in decoration of cakes and other bakery products. Different concentrations (1:1 and 1:2) of pigment were used in paper making process. The products were exposed to sunlight and fluorescent light for 4 h in which sunlight caused higher fading effect. Prodigiosin was also used in soap making at 1, 2 and 3 mg L-1concentration and it gave attractive colour shades to the final products. For candle making, different concentrations (1:5, 2:5 and 3:5) of pigment used were and the study showed that the prodigiosin can be an attractive choice for making colourful candles of different shapes. The potential of prodigiosin as ink for highlighter pen was tested by preparing different compositions in presence of citric acid and glycerol. Results suggested that the concentration >0.25% can be readily used in highlighter pen.